Kesejahteraan Psikologis Guru Sanggar Inklusi Di Kabupaten Sukoharjo - Mellani Agustin; Sri Ernawati (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2024)
This research aims to obtain a picture of the psychological well-being of inclusive studio teachers. There are six dimensions of psychological well-being, namely self-acceptance, positive relations with others, autonomy, environmental mastery, purpose in life, and personal growth. Participants were five teachers at the Inclusion Studio in Sukoharjo Regency. The research was conducted using the case study method. Data collection uses interview techniques. Data were analyzed using thematic data analysis. The results show that all dimensions of psychological well-being play a role in supporting and carrying out work as teachers at the Inclusion Studio in Sukoharjo Regency. Research can be used as an illustration to design interventions that can be used to improve the psychological well-being of Inclusion Studio teachers in Sukoharjo Regency.